A Method to Replace Section with other sections with capacity Equal Tolerance in the case of spandex and flexible - onabi, ammar (Journal of King Abdulaziz University: Engineering Sciences, 2024)
Construction Engineers face difficulties during the execution of metallic construction works that compose standard Profiles or designer in other countries where the designer prescribes profiles which are not common in local area . This will causes sustention of construction works and consequently material and lasses. Those engineers may need a method for replacing these profiles with others. In this research, Author describes a novel method that enables designers to replace supposed metallic profiles Sections (e.g. solid Rectangular, ring section) with new Sections (Box, [ and I sections) provided that the moment of Inertia of the new section equals the moment assuming that the elastic theory is used. In Case the Plastic theory is used, the condition will be the static moment of the new section is equal to static moment of original section. The author evaluated the research results.